Localization of the synovial sarcoma t(X;18)(p11.2;q11.2) breakpoint by fluorescence in situ hybridization. - Knight, J; Reeves, B; Kearney, L; Monaco, A; Lehrach, H; Cooper, C (1992)
A high proportion of synovial sarcomas contain a chromosome translocation t(X;18)(p11.2;q11.2). We have previously used somatic cell hybrids derived from an established cell line, SS255, to map the X chromosome breakpoint to the interval flanked by the markers DXS14 and DXS146. In this study we have examined these hybrids with thirteen additional markers located at Xp11.3-Xcen, by Southern hybridization. Based on these results we have delimited the breakpoint as follows Xpter-DXS228-(UBE1-OATL1-TIMP-DXS226 )-(DXS255-TFE3-ELK1-DXS146)-OATL2- X;18-(DXS14-DXS422-DXS423-DXS674-DXS679)-+ ++Xcen. Confirmation of the breakpoint location has been obtained by analysis of two synovial sarcoma cell lines, SS255 and HA2243, using fluorescence in situ hybridization. A 350kb YAC probe spanning the DXS423 locus hybridized only to the derivative X chromosome, showing that it maps proximal to the breakpoint. Two YAC probes of 300kb and 450kb, containing the OATL2 locus, hybridized to both derivative chromosomes, indicating that these YACs span the translocation breakpoint. Similar results were obtained with both cell lines. The identification of YACs that span the t(X;18) breakpoint now facilitates a strategy for cloning candidate genes from this precisely defined region.